2020
DOI: 10.1039/d0tc03095c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of main and side chain chlorination on the photovoltaic properties of benzodithiophene-alt-benzotriazole polymers

Abstract: In developing organic semiconductor polymers for photovoltaic applications, chlorine substitution has become an effective strategy in replacing fluorine substitution to overcome the drawbacks of low yield and high cost, commonly...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…Thus, we can draw a conclusion from the DMTA and GIWAXS results that our new polymers are completely amorphous. In order to compare PIDT-TXBT with the reported high-performing donor polymers, we also performed DMTA measurement on PM6 and J71 (DMA plots shown in the Supporting Information, Figure S18). However, these two high-performing donor polymers only show sub- T g transitions and no detectable T g , which we believe is a result of the “hairy aggregates” phase described in our previous work .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, we can draw a conclusion from the DMTA and GIWAXS results that our new polymers are completely amorphous. In order to compare PIDT-TXBT with the reported high-performing donor polymers, we also performed DMTA measurement on PM6 and J71 (DMA plots shown in the Supporting Information, Figure S18). However, these two high-performing donor polymers only show sub- T g transitions and no detectable T g , which we believe is a result of the “hairy aggregates” phase described in our previous work .…”
Section: Resultsmentioning
confidence: 99%
“…By comparing device performance and stability of the SM‐OSCs with/without PDINO within these two different active layers (Figure S14 and Table S3, Supporting Information), we found the ETL‐free devices show comparable initial device performance and better device stability, indicating that well performing the ETL‐free SM‐OSCs is not restricted to the H31 :Y6 combination studied here in detail. We also investigated the device performance of PSCs based on blends of two polymers, J71‐Cl and J101 [ 54 ] (structures shown in Figure S15 in the Supporting Information), with 9‐bis(2‐methylene‐((3‐(1,1‐dicyanomethylene)‐6,7‐difluoro)‐indanone))‐5,5,11,11‐tetrakis(4‐hexylphenyl)‐dithieno[2,3‐ d :2′,3′‐ d ′]‐s‐indaceno[1,2‐ b :5,6‐ b ′]dithiophene (IT‐4F) as NFA with and without PDINO and found that both PSCs show lower PCEs without PDINO (Figure S16 and Table S4, Supporting Information). This demonstrates that PDINO enhances the PCE in these PSCs.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing device performance and stability of the SM-OSCs with/without PDINO within these two different active layers (Figure S14 and Table S3, Supporting Information), we found the ETL-free devices show comparable initial device performance and better device stability, indicating that well performing the ETL-free SM-OSCs is not restricted to the H31:Y6 combination studied here in detail. We also investigated the device performance of PSCs based on blends of two polymers, J71-Cl and J101 [54] (structures shown in Figure S15 dithiophene-4,8-dione)] (PM6) and Y6. [38] This shows that omitting the ETL affects the initial performance in these PSCs negatively.…”
Section: Resultsmentioning
confidence: 99%
“…The sub-nanometer surface roughness found for J71:ITIC (R q ¼ 0.55 nm) and J71:IT-4F (R q ¼ 0.80 nm) agrees well with previously reported data for these blends of 0.72 and 0.74 nm, respecively. 41,45 Compared to the J77-based blend films, the R q values of the J71-based blend film are thus slightly lower, but the difference is very small. This suggests that similar nanophase morphology is obtained with triisobutylsilyl side chains as with tripropylsilyl side chains.…”
Section: Resultsmentioning
confidence: 96%